Dietary protein requirement of stunted fi ngerlings of the Indian major carp, Catla catla (Hamilton) during grow-out phase - Ramaswamy, B.; Naveen Kumar, B. T.; Doddamani, Pradeep L.; Panda, Kamalesh; Ramesh, K. S. (Indian Journal of Fisheries, 2013)
A 120 day experiment was conducted to investigate the dietary protein requirement of stunted fi ngerlings of the Indian major carp Catla catla, during the grow-out period. Fingerlings of average weight 7.10 g were fed on three different formulated diets with varying protein levels (20, 25 and 30%). Growth, survival, protein effi ciency ratio (PER), food conversion ratio (FCR), specifi c growth rate (SGR) and ratio of protein deposition in the carcass were measured. Water quality parameters were analysed and found to be optimum for culture. The results indicated that fi sh fed diet containing 25% protein showed better growth performance in terms of the parameters measured.